Optimization of the snowflake divertor for power and particle exhaust on NSTX–U. (May 2019) - Vail, P.J.; Izacard, O.; Kolemen, E.
Highlights: A model of diffusive transport and partitioning of power in the SFD is derived. The best SFD configurations for heat flux reduction are determined. The optimal location for the entrance to a divertor cryopump on NSTX-U is computed. UEDGE simulations indicate that redistribution of SOL power occurs due to pumping. Abstract: In this paper, simple analytical modeling and numerical simulations performed with the multi-fluid edge transport code UEDGE are used to identify optimal snowflake divertor (SFD) configurations for heat flux mitigation and sufficient cryopumping performance on the National Spherical Torus eXperiment Upgrade (NSTX–U). A model is presented that describes the partitioning of sheath-limited SOL power and particle exhaust in the SFD as a result of diffusive transport to multiple activated strike points. The model is validated against UEDGE predictions and used to analyze a database of 70 SFD-minus equilibria. The optimal location for the entrance to a divertor cryopumping system on NSTX–U is computed for enabling sufficient pumping performance with acceptable power loading in a variety of SFD-minus configurations. UEDGE simulations of one promising equilibrium from the database indicate that a significant redistribution of power to the divertor legs occurs as a result of neutral particle removal near one of the SFD-minus strike points in the outboard scrape-off layer. It is concluded that pump placement at the optimal location is advantageous as the large number of compatible equilibria reduces the precision required of real-time SFD configuration control systems and enables acceptable divertor solutions even if UEDGE-predicted power redistribution slightly reduces the achievable pumping performance.